Pattern of Pediatric Uveitis Seen at a Tertiary Referral Center from India. (3rd July 2016) - Ganesh, Sudha K.; Bala, Aparna; Biswas, J.; Ahmed, Arshee S.; Kempen, John H.
Abstract: Aim : To analyze the profile, etiology, complications, medical and surgical management, and visual outcome among pediatric uveitis patients seen at a referral uveitis clinic in India. Design : Retrospective cohort study, tertiary hospital setting. Methods : Records between January 2007 and April 2010 were reviewed for patients with uveitis who were 0–18 years of age. Uveitis diagnosis was based on SUN criteria; complications, medical and surgical management, and visual outcome were evaluated. Results : Among 190 children with uveitis, 64.2% were boys and 112 had unilateral disease. The median age at presentation was 11 years. Ninety-nine (52%) had anterior, 49 (26%) intermediate, 27 (14%) posterior, and 15 (7.9%) panuveitis. Infectious uveitis was present in 44 patients, of which 21 cases (48%) were posterior uveitis. Parasitic, tuberculous, and viral infectious uveitis was encountered. A total of 174 patients were followed over 315.5 person-years (median = 1.35 years). Seventy-seven (40.5%) children had complications related to uveitis. Forty-six out of 77 complications noted were complicated cataracts. Surgical procedures were done in 46.9% (15%/100 person-years). The visual acuity improved by two Snellen lines in the uveitic eyes, following therapy in 120 children, was stable in 40 children, and worsened in 14 children. Follow-up visual acuity was missing for 16 children. Conclusion : A large proportion of pediatric uveitis cases experienced complications of uveitis, mostly prior to presentation for subspecialty management. These often required surgical management, most commonly to clear the visual axis of cataract for visual rehabilitation and to prevent amblyopia. In most cases, tertiary management was associated with visual improvement. The results suggest that subspecialty management can result in improvement of the clinical course of pediatric uveitis.